2012
DOI: 10.1021/ma300593g
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of End-Linked PEG/PDMS Hydrogels

Abstract: Poly(ethylene glycol) (PEG)/polydimethylsiloxane (PDMS) hydrogels were synthesized by cross-linking norbornene end-functionalized polymers with a tetrafunctional thiol using thiol−norbornene chemistry. The swelling capacity and mechanical properties, including the Young's modulus (E) and fracture toughness (G c ), of the hydrogels were characterized and quantified as a function of the volume fractions of PEG and PDMS. E and G c increased simultaneously with the volume fraction of PDMS. The moduli of the hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 36 publications
2
66
0
Order By: Relevance
“…56,57,58 PEG and PS were chosen as model co-network components for several reasons. Many studies on PS-PEG block copolymers have been reported, and their phase behavior is well known.…”
Section: Resultsmentioning
confidence: 99%
“…56,57,58 PEG and PS were chosen as model co-network components for several reasons. Many studies on PS-PEG block copolymers have been reported, and their phase behavior is well known.…”
Section: Resultsmentioning
confidence: 99%
“…combined linear PEG-norbornene with poly(dimethylsiloxane)-norbornene (PDMS-norbornene) and used tetra-functional PEGSH as cross-linker for UV light-mediated thiol-norbornene photopolymerization. 42-43 The resulting hydrogels are highly elastic and strong and should be useful for applications requiring high resilience and strength.…”
Section: Macromers Developed For Forming Thiol-norbornene Hydrogelsmentioning
confidence: 99%
“…For this purpose, we reported the preparation of homogeneous amphiphilic gels by the cross-linking of hydrophilic tetra-arm poly(ethylene glycol) and hydrophobic linear poly(dimethylsiloxane) to form PEG−PDMS gels. 30 In contrast to the conventional way of copolymerization, 31 this reaction does not require cross-linkers. 32 Therefore, the resultant gels are homogeneous similar to the inhomogeneity-free gels we have reported using only tetra-arm PEG units.…”
Section: ■ Introductionmentioning
confidence: 99%